Pengaruh Remunerasi terhadap Kinerja ASN dengan Budaya Organisasi sebagai Variabel Moderating - Sandri Niddin; Henri Agustin; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to examine the effect of remuneration on the performance of state civil servants with organizational culture as a moderating variable. This study used a survey research design with data analysis using Partial Least Square (PLS). Respondents in this study were civil servants at the Public Works and Spatial Planning Office; and the Department of Education and Culture, amounting to 136 people. The results showed that remuneration can improve employee performance. In addition, the results of the study cannot prove that organizational culture as a moderating variable can strengthen the effect of remuneration on the performance of state civil servants, because the organizational culture that is implemented is not yet strong